The Development of Science Learning Device Based on Interconnected Integration in Increasing Critical and Creative Thinking Students' - Hilda, Lelya; Lubis, Rosimah; Daulae, Tatta Herawati (SCAD Independent, 2020)
Interconnected Integration based learning is really needed to narrow the dualism space or the science dichotomy which separates between general education and religion education which then has an impact on the separation and segregation of religious awareness and general science. In the learning process, critical and creative thinking skills are very important, because it can make people become more mentally flexible, open and easy to adapt to various situations and problems. The type of this research was research and development. The development model used in this study was a modification of Borg and Gall's development stage which states that there were 10 stages in research and development. The research results showed that the instructional materials produced had very good validity (89%), very practical (91.19% by teachers and 86.21% by students and very efficient with the average critical and creative thinking (pretest) of students; 66.31 and posttest 80.26, and the results of the t-test count = 15.712 with sig 0.00 <0.05. This shows that there were significant differences before being treated and after treated by using the interconnection approach in improving students' critical and creative thinking.